Secondary Traumatic Stress, Mental State, and Work Ability in Nurses—Results of a Psychological Risk Assessment at a University Hospital - Bock, Christian; Heitland, Ivo; Zimmermann, Tanja; Winter, Lotta; Kahl, Kai G. (Frontiers in Psychiatry, 2020)
Psychological risk assessment is a legal obligation for companies and part of occupational safety and employment protection in Germany. However, data from psychological risk assessments in nursing staff are scarce, although this population is at increased risk for secondary traumatic stress by patient experienced trauma. Therefore, our study aimed at examining the frequency of reported secondary trauma events, secondary traumatic stress, and its possible consequences for psychological well-being and work ability in nurses. N = 320 nurses (n = 280 female) were assessed at a University Hospital in Germany as part of the psychological risk assessment. Secondary traumatic events, secondary traumatic stress, and symptoms of depression and anxiety were measured using self-report questionnaires (PHQ-2, GAD-2), and work ability was assessed using a modified version of the questionnaire for workplace analysis (KFZA). Of 320 nurses, 292 (91.2%) experienced secondary trauma, and 74 nurses (25.3%) reported secondary traumatic symptoms. Nurses with secondary traumatic symptoms had higher depression and anxiety scores compared to nurses without secondary trauma experience, and to nurses with secondary trauma experience but without secondary traumatic stress. Further, nurses with secondary traumatic stress reported significantly reduced work ability, social support and control over work, and increased emotional strain and labor time. Nurses with secondary traumatic stress are at increased risk of developing major depression and anxiety disorders, and particularly need support in overcoming secondary traumatic experiences. Psychological risk assessment is a useful tool to identify groups at risk, and pave the way to implement strategies to improve mental well-being and prevent work ability in high risk groups